Islamic Republic of Mauritania : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses implementation of the Poverty Reduction Strategy Paper (PRSP) in Mauritania. The second phase of the PRSP is accompanied by a Medium-Term Expenditure Framework (MTEF) for 2006-10. MTEF determines the overall cost of the action plan in terms of both current and capital expenditure, and defines the source of the financing needed for its implementation. The financial support of Technical and Financial Partners, which will remain necessary for a time, will gradually give way to technical and strategic support, with emphasis on the transfer of technology and know-how.